An analysis of the maternal health referral system: a case study of the BAKSOKUDA system in Central Lombok, Indonesia - Sastrawan, Sastrawan; Sulaiman, Lalu; Erawati, Eva (International Journal of Public Health Science (IJPHS), 2025)
Maternal mortality remains a critical concern in Central Lombok, with over 50% of maternal deaths in hospitals involving cases referred through the BAKSOKUDA referral system. This suggests potential failures within the referral process, raising concerns about systemic issues compromising maternal health emergencies. This research uses a qualitative case study methodology to investigate the BAKSOKUDA system, aiming to identify the challenges contributing to high maternal mortality and provide insights for improving healthcare outcomes. Data were collected through semi-structured interviews with eleven participants: midwives, doctors, nurses, and a hospital manager. Thematic analysis identified several critical issues: communication breakdowns, inconsistent adherence to protocols, difficulties in securing family cooperation, inadequate infrastructure, and lack of community support for blood donation. These findings highlight four interrelated components—human resources, the professional environment, patients and families, and community support—as central to effective maternal health systems. To address these challenges, the study recommends enhancing communication and protocol adherence, providing comprehensive midwife training, promoting cultural sensitivity, and addressing systemic issues like ambulance availability. Strategic planning, resource allocation, and regional coordination are essential to improving infrastructure and ensuring effective referrals. The findings stress the need for a holistic approach, continuous improvement, and active community engagement to optimize maternal care.